Research Progress on Natural Diterpenoids in Reversing Multidrug Resistance - Deng, Zhuo-fen; Bakunina, Irina; Yu, Hua; Han, Jaehong; Dömling, Alexander; Ferreira, Maria-José U; Zhang, Jian-ye (Frontiers in Pharmacology, 2022)
Multidrug resistance (MDR) is one of the main impediments in successful chemotherapy for cancers in cancer treatment. Overexpression of ATP-binding cassette (ABC) transporter proteins is one of the most important mechanisms of MDR. Natural products have their its unique advantages in reversing MDR, among them which diterpenoids have attracted great attention of the researchers around the world. This review article summarizes and discusses the research progress on diterpenoids in reversing MDR. Keywords: Cancer; Chemotherapy; Multidrug Resistance; Natural Products; Diterpenoids